Gendered society - Kimmel, Michael S (OUP, 1906)
Thoroughly updated and revised, the third edition of The Gendered Society explores current thinking about gender, both inside academia and in our everyday lives. Michael S. Kimmel challenges the claim that gender is limited to women's experiences--his compelling and balanced study of gender includes both masculine and feminine perspectives. Part 1 examines the latest work in biology, anthropology, psychology, and sociology; Part 2 provides an original analysis of the gendered worlds of family, education, and work; and Part 3 explores gender interactions, including friendship and love, sexuality, and violence. Kimmel makes three bold and persuasive statements about gender. First, he demonstrates that gender differences are often extremely exaggerated; in fact, he argues that men and women have much more in common than we think they do. Kimmel also challenges the pop psychologists who suggest that gender difference is the cause of inequality between the sexes; instead, he reveals that the reverse is true--gender inequality itself is the cause of the differences between men and women.Finally, he illustrates that gender is not merely an element of individual identity, but a socially constructed institutional phenomenon. A new chapter on media examines the portrayal of gender in one of the most powerful--and provocative--social institutions. Of particular interest to students, Kimmel's analysis of this dynamic, image-driven industry makes the study of gender relevant in an immediate and tangible way. Essential reading for both students and scholars, The Gendered Society is an authoritative, incisive, and lively statement about contemporary gender relations from one of the country's foremost thinkers on the subject. Kimmel's companion text, The Gendered Society Reader, Third Edition (OUP, 2008), provides a perfect complement for classroom use.
Keywords: Sex role; Sex differences (Psychology)